Current-controllable fully-integrated inductor simulator using CCCIIs - Sedef, H.; Sagbas, M.; Acar, C. (TAYLOR & FRANCIS LTD, 2008)
A novel current controllable floating or grounded inductor simulator circuit with minimum elements is proposed. The circuit uses two dual output- second generation current controlled conveyors (DO-CCCIIs) with parasitic resistance at terminal X and one grounded capacitor externally connected. Proposed circuit is suitable for fully integrated circuit design. Analysis and simulation results are included.
Keywords: analogue electronics; inductor simulator; current conveyors; active networks; Engineering